2014
DOI: 10.1603/en13162
|View full text |Cite
|
Sign up to set email alerts
|

Developing Monitoring Techniques for the Invasive Goldspotted Oak Borer (Coleoptera: Buprestidae) in California

Abstract: The goldspotted oak borer, Agrilus auroguttatus Schaeffer (Coleoptera: Buprestidae), is an invasive species that has colonized oak woodlands in southern California. To better define its seasonal flight activity, assist with forest and integrated pest management activities, and define the current distribution in California, an effective monitoring technique for A. auroguttatus is necessary. We assessed the efficacy of two colors of flight-intercept prism traps, the placement of these traps at three heights, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…This trend has also been documented for A. planipennis [48] and A. auroguttatus [60], although both of these species also show a preference for green traps [61,62]. In this study A. biguttatus was not caught on any green traps, however, recent studies showed green canopy-based traps did catch A. biguttatus, albeit in very low numbers [63].…”
Section: Discussionsupporting
confidence: 71%
“…This trend has also been documented for A. planipennis [48] and A. auroguttatus [60], although both of these species also show a preference for green traps [61,62]. In this study A. biguttatus was not caught on any green traps, however, recent studies showed green canopy-based traps did catch A. biguttatus, albeit in very low numbers [63].…”
Section: Discussionsupporting
confidence: 71%
“…If aggregation is a key factor in colonization of oaks by A. auroguttatus , effective management of the pest might focus on removal of moderately to severely infested trees and insecticide application to lightly infested trees. This management activity may require more effective early detection techniques than are available presently …”
Section: Discussionmentioning
confidence: 99%
“…Agrilus auroguttatus holes are uniquely sized and shaped and, with training, can be distinguished from emergence holes produced by other woodborers in California oaks . In contrast, other life stages are impractical to monitor: adults are rarely observed and the currently recommended detection trap is not very effective; eggs are laid in bark crevices and almost impossible to find; larvae developing within the tree cannot be observed without destructive sampling which would have killed trees and jeopardized our long‐term monitoring of insecticide efficacy and tree health. Destructive sampling was also not acceptable at these privately owned sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Coleman and Seybold (2008), purple prism glue-coated traps (developed by Francese et al 2008) on a 3 m pole with an ethanol attractant were found to be effective. In another study, Seybold et al (2010) found that purple traps had higher capture rates at a height of 3 m, while green traps had more captures at a height of 4.5 m. Comparing colours of flight-intercept prism traps (three sides, 35.6 by 59.7 cm, Francese et al, 2008), Coleman et al (2014) found that purple and green were equally effective at catching A. auroguttatus males, while purple traps were more effective for capturing females. In another study, Seybold et al (2010) found that purple traps had higher capture rates at a height of 3 m, while green traps had more captures at a height of 4.5 m. Comparing colours of flight-intercept prism traps (three sides, 35.6 by 59.7 cm, Francese et al, 2008), Coleman et al (2014) found that purple and green were equally effective at catching A. auroguttatus males, while purple traps were more effective for capturing females.…”
Section: Trapsmentioning
confidence: 99%